Efektifitas Foot Spa Diabetic terhadap Nilai Ankle Brachial Index pada Pasien Diabetes Mellitus Tipe II - Rizkan Halalan Djafar; Busjra M. Nur; Rohman Azzam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to find out the effectiveness of diabetic foot spa towards ankle brachial index. Design of this study is Quasy-Experiment with two group. The population were all diabetes mellitus patients type 2 in Public Health Centre Wawonasa Manado. Number of sample was 32 person, divided into 2 group, that are treatment group during 3 and 5 time, with 16 person each group, taken by purposive sampling technique. Data analyzed by Mann-Whitney test with Î±=0.05. Study results on difference between ABI treatment 3 dan 5 time. Analysis of Mann-Whitney test P=0.112> Î±=0.05, with average ABI in treatment group during 3 and 5 time pre test 0.012 and post test 0.0562, which means diabetic foot spa 3 and 5 time is effective towards ABI. Keywords: Ankle Brachial Index, DM Type 2, Foot Spa Diabetic